1979
DOI: 10.1016/s0006-3495(79)85172-3
|View full text |Cite
|
Sign up to set email alerts
|

Chromophore equilibria in bacteriorhodopsin

Abstract: An investigation of the dark equilibria between different chromophores of bacteriorhodopsin (BR) and studies of the kinetics of their interconversion and photochemical activity have led to the following conclusions. (a) A component of the 605-nm chromophore of BR decays in the millisecond range and is likely to be identical to the intermediate O of the photochemical cycle of BR and is assumed to be formed from the purple complex (PC) by the binding of one proton to BR. (b) An acidic form the PC, PCaL-, arises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
171
1
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(187 citation statements)
references
References 19 publications
14
171
1
1
Order By: Relevance
“…In addition to the function of Asp ~5 as proton accepter in M, it has also been suggested that a carboxyl group near the Schiff base is involved in the purple-toblue transition of bacteriorhodopsin [12][13][14]. The blue form, BRbt,,c, is obtained either by acid titration of removal of cations [15--18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the function of Asp ~5 as proton accepter in M, it has also been suggested that a carboxyl group near the Schiff base is involved in the purple-toblue transition of bacteriorhodopsin [12][13][14]. The blue form, BRbt,,c, is obtained either by acid titration of removal of cations [15--18].…”
Section: Introductionmentioning
confidence: 99%
“…Removal of these cations from purple membrane patches (6,7) or acidification (2,8,9) causes a color transition from purple to blue. The absorption maximum of the retinal chromophore is believed to be primarily regulated by the electrostatic interactions between the charged or polar side chains of amino acids and the PSB, as well as certain carbon atoms along the retinal electronic system (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Time-resolved resonance Raman spectroscopy has been used to show that the Schiff base linkage is protonated in BRsTo, unprotonated in M412, and protonated once again in 0640 [4 6]. Studies of an illumination-independent acid-induced species, which apparently represents stabilization of phototransient 0640 at low pH, suggest that protonation ofa carboxylgroup of an amino acid side chain is involved in the formation of the 0640 intermediate [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…(i) Interacting directly with the Schiff base nitrogen [8,9]; (ii) Interacting with the/3-ionone ring of retinal to form a 'charge stabilized' intermediate [ 10]; (iii) Participating in a sequence of proton-translocating groups [4,11]; or (iv) Forming ion-pairs within the membrane with the positively charged groups of arginine and/or lysine [11 13]. Since the primary sequence of BR has been reported [14], it is now possible by chemical modification techniques to gain information on the role of specific amino acid residues in proton translocation.…”
Section: Introductionmentioning
confidence: 99%